Bioactive coating on stainless steel 316L through sol-gel method - Jafari, Sajjad (2012)
In this work hydroxyapatite coating through sol-gel method on stainless steel 316 L was investigated. Biocompatible additives such as P2O5, Na2CO3, KH2PO4 and HA commercial powder were used for preparation of hydroxyapatite sol-gel. Corrosion behavior of the ground and passivated stainless steel was evaluated. Characterization of the coated samples was performed by using SEM and XRD. The results showed that by increasing the sintering temperature, a denser structure of hydroxyapatite was obtained, and volume fraction and size of porosities decreased. Thick hydroxyapatite coatings with a thickness range of 50-70 µm free from cracks were obtained.